Aspek Hukum Pidana terhadap Tindak Pemerasan oleh Lembaga Swadaya Masyarakat di Indonesia - Ahmad Wildan Firdaus; M. Hikmal Ash Siddiqie; Najwa Abelia Batubara; Mutiara Anand; Yonatal Siallagan (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
Extortion is an act committed to gain benefits for oneself or others by exerting pressure and causing harm to another party. This phenomenon often involves individuals from non-governmental organizations (NGOs) and has repeatedly been brought to trial, although similar cases continue to emerge. This study applies both normative and empirical juridical approaches to examine the criminal law aspects of extortion committed by NGOs. The findings indicate that criminal sanctions for perpetrators are regulated in the Indonesian Criminal Code (KUHP), particularly in Chapter XXIII Articles 368 and 369, which provide the legal basis for enforcing sanctions against such practices.